Comparison of intrathecal dexmedetomidine and intrathecal fentanyl as an adjuvant to bupivacaine during spinal anaesthesia for lower limb orthopedic surgery - Agrawal, Dipty; Niyati Sinha,; Shiv Kumar Singh, (Asian Journal of Medical Sciences, 2023)
Background: In this study, we have compared the addition of fentanyl 25 mcg and dexmedetomidine 5 mcg to 15 mg of 0.5% hyperbaric bupivacaine for spinal anesthesia separately for patient undergoing lower limb orthopedic surgery. Dexmedetomidine is an α-2 adrenoreceptor agonist and it can prolong the motor and sensory block for long spinal anesthesia. It act by binding to presynaptic C-fiber and postsynaptic dorsal horn neurons. The analgesic action is a result of depression of release of C-fiber transmitters and hyperpolarization of postsynaptic dorsal horn neurons. Aims and Objectives: The present study compares the onset, duration of sensory and motor block, postoperative analgesia, hemodynamic changes, and adverse effects of intrathecal dexmedetomidine and intrathecal fentanyl as an adjuvant to bupivacaine during spinal anesthesia for lower limb orthopedic surgery. Materials and Methods: Patient was randomly grouped by close-envelope technique into the three equal group of 30 in each group. Total 90 patients were including in this study. The blind nature of the study was maintained and the study drug is given according as, Group-1: 15 mg of 0.5% hyperbaric bupivacaine. (Control group), Group-2: 15 mg of 0.5% hyperbaric bupivacaine with 25 mcg of fentanyl, and Group-3: 15 mg of 0.5% hyperbaric bupivacaine with 5 mcg dexmedetomidine for spinal anesthesia. Results: Patients in dexmedetomidine Group-3 had a significantly longer sensory (160±18.5 min) and motor block (242±22 min) time as compared to patients in fentanyl and control group (P<0.001). The time to first request of analgesic in the post-operative period was also longer in dexmedetomidine group (245±3.6 min) when compared to bupivacaine and fentanyl in which it was 125±1.0 min and 220±2.5 min, respectively (P<0.001). Conclusion: We concluded that intrathecal dexmedetomidine with bupivacaine for spinal anesthesia is associated with prolong motor and sensory block then fentanyl 25 μg with bupivacaine and bupivacaine alone.